Serum peptides, represented by complement 3f des‐arginine, are useful for prediction of the response to pegylated interferon‐α plus ribavirin in patients with chronic hepatitis C. Issue 7 (6th December 2012) - Noguchi, Yohei; Kurokawa, Manae S.; Okuse, Chiaki; Matsumoto, Nobuyuki; Nagai, Kouhei; Sato, Toshiyuki; Arito, Mitsumi; Suematsu, Naoya; Okamoto, Kazuki; Suzuki, Michihiro; Itoh, Fumio; Kato, Tomohiro
<x xml:space="preserve">Abstract</x> Aim Biomarkers predicting sustained virological response (SVR) to pegylated interferon‐α plus ribavirin (PEG IFN‐α/RBV) were investigated. Methods Peptides in pretreatment sera from 107 patients with hepatitis C virus (HCV) genotype 1 were comprehensively analyzed by mass spectrometry. Ion intensity of the peptides was used to generate discriminant models between the responders who achieved SVR (R) and the non‐responders (NR) to PEG IFN‐α/RBV. Results In total, 107 peptides were detected in a training set (n = 23). A discriminant model using a peptide, complement 3f des‐arginine (C3f‐dR), showed sensitivity of 35% and specificity of 94% for SVR prediction in a testing set (n = 68). In all the R and NR (n = 96), an area under the receiver–operator curve (AUROC) of 0.64 in the C3f‐dR model was increased to 0.78 by addition of platelet (PLT) counts (C3f‐dR/PLT model). Another model using the 107 peptides (AUROC, 0.77) also showed higher AUROC (0.79) by addition of hemoglobin (Hb), body mass index (BMI) and age (107P/Hb/BMI/Age model). The sensitivity and specificity of the C3f‐dR/PLT model were 59% and 88%, and those of the 107P/Hb/BMI/Age model were 70% and 92%, respectively. The C3f‐dR/PLT model showed high AUROC (0.82), similar to that of interleukin‐28B rs8099917 genotype analysis (0.86) in the 45 tested patients. Prediction by the combination of the C3f‐dR/PLT model, the 107P/Hb/BMI/Age model and the rs8099917 genotype analysis was accurate in 44 out of the 45 patients (AUROC, 0.95). Conclusion Serum peptides, especially C3f‐dR, would be useful predictors for SVR to PEG IFN‐α/RBV. The complements may be involved in the HCV elimination.